SMART TRAFFIC SYSTEM - Pranav S Ram,; Rajan, Radhika; Rahul MR,; Deepika M P, (International Journal of Psychosocial Rehabilitation, 2020)
An increase in the number of vehicles which is not followed by the number of roads can lead to excesive congestion, especially in big cities. The regulation of Law Number 22, Year 2009 explains that there are seven types of vehicles that are prioritized on the road. Conventional methods of traffic light systems are unable to deal with the ongoing issues surrounding congestion. The current traffic light models are not suitable to tackle problems such as traffic jams, ease of access for emergency vehicles and the prevention of accidents. Our present traffic light systems are based on microcontrollers and microprocessors which are predefined hardware which functions according to the programmed code. They are not flexible on the real time basis. Due to the fixed time intervals of red, yellow and green signals, the waiting time is more and the vehicle uses more fuel. The proposed project will focus on two aspects of implementation. First and foremost, to make traffic light controlling more efficient. This system will intelligently decide when to alternate signals based on the intensity of traffic on each lane, which is detected by sensors on each lane. This will ultimately increase the efficiency of the traffic flow. The second is a manual mode which allows authorized officials to control the signals. This is intended for use during the time of emergency.